A world beyond work? : Labour, money and the capitalist state between crisis and utopia - Dinerstein, Ana Cecilia; Pitts, Frederick Harry (SocietyNow., 2021)
Sensing a future beyond work lurking in an age of crisis, the 'post-capitalist' utopias of today spread the idea of a permanent escape from work aided by the automation of production, a universal basic income and the reduction of working hours to zero. By skilfully unpicking the political economy of contemporary work and its futures, this book mounts a forceful critique of the post-work society vision. Dinerstein and Pitts reveal that transitional measures towards a world beyond work do not do enough to break away from the key features of capitalist society, and instead potentially stifle the capacity for transformative social change. Proposing an innovative alternative, the authors envision the construction of 'concrete utopias' that shape and anticipate non-capitalist futures.